2005
DOI: 10.1097/01.sla.0000189115.94847.f1
|View full text |Cite
|
Sign up to set email alerts
|

The Notch Signaling Pathway Is Related to Neurovascular Progression of Pancreatic Cancer

Abstract: The Notch pathway most likely regulates neurovascular development in pancreatic cancer. Activation of this signaling pathway by constitutive Notch-1 mutants and by Jagged-1 causes an angiogenic and invasive tumor phenotype. Specific blockade of Notch signaling may therefore be beneficial for patients with pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 38 publications
4
65
1
2
Order By: Relevance
“…It consists of two cleavages, occurring at the extracellular side, followed by a third cleavage that liberates the intracellular Notch receptor domain, which is translocated to the cell nucleus (40,41), where it regulates the balance between cell differentiation and stem cell proliferation, during the development of numerous tissues, including the pancreas (34,42). It is likely that this latter form participates in neoplastic cell transformation in several organs, such as the cervix, uteri, lung, breast, nerve tissue and also in the pancreas (43)(44)(45)(46)(47). However, the cases of staining in PDAC that we found were uniformly cytoplasmic, with no nuclear Notch2 and Notch3 being observed in any case; it is thus likely that tumors expressing nuclear Notch2 and Notch3 had been found to be non-resectable.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of two cleavages, occurring at the extracellular side, followed by a third cleavage that liberates the intracellular Notch receptor domain, which is translocated to the cell nucleus (40,41), where it regulates the balance between cell differentiation and stem cell proliferation, during the development of numerous tissues, including the pancreas (34,42). It is likely that this latter form participates in neoplastic cell transformation in several organs, such as the cervix, uteri, lung, breast, nerve tissue and also in the pancreas (43)(44)(45)(46)(47). However, the cases of staining in PDAC that we found were uniformly cytoplasmic, with no nuclear Notch2 and Notch3 being observed in any case; it is thus likely that tumors expressing nuclear Notch2 and Notch3 had been found to be non-resectable.…”
Section: Discussionmentioning
confidence: 99%
“…The Notch signaling pathway is involved in the carcinogenesis, progress, invasion and neurovascular formation of many malignant tumors (22,(33)(34)(35). The Notch signaling pathway can regulate MMP-2, MMP-9 and VEGF (22,(36)(37)(38)(39)(40), which are important in the processes of invasion and metastasis of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is clear that alterations in Notch signaling are associated with carcinogenesis of the pancreas. We and others have found that Notch signaling is frequently deregulated in human pancreatic cancers (Wang et al, 2006e;Wang et al, 2006a;Buchler et al, 2005). High expression of Notch, which inhibits apoptosis, has been found in pancreatic cancers.…”
Section: Activation Of Oncogenesmentioning
confidence: 99%